Tafakkur Spiritual dalam Perspektif Al Quran dengan Metode Tafsir Tematik - Haromain, Imam; Hakim, Lukmanul (Jurnal Pendidikan Islam, 2024)
This study focuses on the exploration of spiritual contemplation (tafakkur) in the Quran using the thematic interpretation method. Tafakkur, or deep spiritual reflection, is an essential aspect in understanding the teachings of the Quran. The aim of this research is to identify and analyze spiritual themes within the Quran and elucidate how tafakkur is employed to comprehend these meanings. The thematic interpretation method is utilized to categorize and investigate verses related to the spiritual dimension. The results of this study are expected to provide new insights into the spiritual richness within the Quran.